Smart blind-pedestrian traffic light and smart cane with earpiece / Nurin Aqilah Mohamad Othman Omar … [et al.] - Mohamad Othman Omar, Nurin Aqilah; Hasbullah, Nur’Ain Nadhira; Amran, Fatin Amily; Mohd Azman, Irdina Nur Batrisyia; Harun, Norazman (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
The purpose of this report is to explain about the product that had been innovated by us and how to use it properly. R Saravanan, who works as office assistant, said, “We cannot cross the road without someone’s help. Sometimes nobody turns up to help us and we have to cross the road on our own so we can catch buses.” (R Saravanan Jul 11, 2019). Our set of products has the potential for commercialization because these products can be used by blind people.